Akses Informasi Pertanian Melaui Media Komunikasi Pada Kelompok Tani di Kabupaten Sambas dan Kota Singkawang - harmoko erik darmansyah harmoko (Universitas Muhammadiyah Yogyakarta, 2016)
Access to agricultural information to farmers vegetable and rice farmers could be affected by the availability of communications media and internal factors and external factors farmers. With the method of the survey, respondents came from two clusters namely vegetable growers and rice farmers. Each cluster number of respondents 55 people , bringing the total respondents 110 farmers. The results showed that the factors that influence farmers to access agricultural information is a cosmopolitan level . While agricultural information needed vegetable farmers is marketing , the rice farmers the information needed is the technology of production. It shows there is a difference between access to agricultural information between farmers vegetable and rice farmers